2019
DOI: 10.1016/j.hpb.2019.03.373
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of cholecystectomy in octogenarians. Analysis of a single center series of 316 patients

Abstract: Introduction: Cholecystectomy is the treatment of choice for symptomatic cholelithiasis. However, outcomes for patients over 80years of age are not well studied. The primary aim of this study was to describe the safety and feasibility of cholecystectomy, including in the acute setting, in a cohort of patients80 years of age. Material and methods: A retrospective study of patients aged80 years submitted to cholecystectomy at a single institution from January 2013 to January 2018 was performed. Severity of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Early LapC for AC patients is associated with a mortality rate of less than 1%, 15 and higher rates ranging from 1.6% to 4.8% are reported from studies based on cohorts above the age of 80 years 16–18 . In the past 9 years, there was no mortality in AC patients receiving early cholecystectomy at our institution, which infers that the decisions on the indication for early surgery, surgical technique, and postoperative care were appropriate.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Early LapC for AC patients is associated with a mortality rate of less than 1%, 15 and higher rates ranging from 1.6% to 4.8% are reported from studies based on cohorts above the age of 80 years 16–18 . In the past 9 years, there was no mortality in AC patients receiving early cholecystectomy at our institution, which infers that the decisions on the indication for early surgery, surgical technique, and postoperative care were appropriate.…”
Section: Introductionmentioning
confidence: 57%
“…Early LapC for AC patients is associated with a mortality rate of less than 1%, 15 and higher rates ranging from 1.6% to 4.8% are reported from studies based on cohorts above the age of 80 years. [16][17][18] In the past 9 years, there was no mortality in AC patients receiving early cholecystectomy at our institution, which infers that the decisions on the indication for early surgery, surgical technique, and postoperative care were appropriate. The aims of this study were (1) to compare the specific characteristics of early LapC for AC between different age groups, (2) to identify predictive risk factors of postoperative complications for each group, and (3) to build a new, simpler riskassessment system.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Despite that, laparoscopic cholecystectomy is currently considered the gold standard in the treatment of acute cholecystitis in the elderly 6 . Laparoscopic cholecystectomy can be safely performed in many patients of up to 85 years, as previously demonstrated 7 . However, the optimal management of acute cholecystitis in patients older than 90 years is less clear.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, for this reason, there were increased chances of complications, conversion rate, and increased use of drains in the surgery. A study by Serna concluded that there is no difference in early cholecystectomy and interval cholecystectomy outcomes in cases of mild to moderate acute cholecystitis [ 24 ]. A study by Fuks went on further to conclude that the outcomes of early cholecystectomy in patients less than the age of 75 years had a similar result compared to patients more than 75 years of age [ 25 ].…”
Section: Discussionmentioning
confidence: 99%